Potensi Tumbuhan Kelakai (Stenochlaena palustris (Burm.F.) Bedd.) asal Kalimantan Tengah sebagai Afrodisiaka - Fahruni Fahruni; Rezqi Handayani; Susi Novaryatiin (Jurnal Surya Medika (JSM), 2018)
The necessity of traditional medicine is efficacious as aphrodisiac increasing every year. The Dayak community believes that Kelakai roots have efficacy as an aphrodisiac drug, but no studies were conducted relating to the efficacy of the Kelakai roots. Traditional medicinal products are efficacious as aphrodisiac have a hormone-like effect, usually contain active ingredients that have estrogenic properties among other things, progesterone, androgenic, adaptogenic, and ketogenic. Materials that are androgenic or adaptogenic nature helps maintain and restore stamina. This research was aimed to determine the content of the active compound on the Kelakai roots that efficacious as an aphrodisiac and to determine the profile of Thin Layer Chromatography (TLC) of active compound contained in Kelakai roots. This study used the identification method of chemical compounds such as starches and aleurone, tannins, catechols, flavonoids, alkaloids, saponins, and steroids for simplicia powder and ethanol extract of Kelakai roots. The extraction of Kelakai roots done by soxhletation and TLC used to identify a specific chemical compound. The result showed that Kelakai Roots contain active compounds potentially aphrodisiac namely alkaloids and saponin. While the TLC profile obtained is the presence of stains on the appearance of a non-polar eluent (Chloroform: Ethyl Acetate) with a ratio of 7: 3, 8: 2, 9: 4 with each Rf value is 0.70 cm (7: 3), 0.94 cm (8: 2) and 0.94 cm (9: 4). This research reported for the first time the potential of Kelakai roots as an aphrodisiac. Thus, further work will focus on the study of the pharmacological effects of Kelakai roots.